2017
DOI: 10.1080/09593330.2017.1320433
|View full text |Cite
|
Sign up to set email alerts
|

Bio-energy generation in an affordable, single-chamber microbial fuel cell integrated with adsorption hybrid system: effects of temperature and comparison study

Abstract: ACFF: activated carbon fiber felt; APHA: American Public Health Association; CE: Coulombic efficiency; COD: chemical oxygen demand; ECG: electrocardiogram; GAC: granular activated carbon; GFB: graphite fiber brush; MFC: microbial fuel cell; MFC-AHS: microbial fuel cell integrated with adsorption hybrid system; MFC-GG: microbial fuel cell integrated with graphite granules; POME: palm oil mill effluent; PTFE: polytetrafluoroethylene; SEM: scanning electron microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, all of these results suggest that different bacteria can work at different temperatures and MFCs can be operated with a wide range of temperatures . The temperature also affects the performance of MFCs, in terms of COD removal, which increases with increasing temperature. ,, Thus, the role of the temperature is vital for not only the energy generation performance of MFCs but also wastewater treatment.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, all of these results suggest that different bacteria can work at different temperatures and MFCs can be operated with a wide range of temperatures . The temperature also affects the performance of MFCs, in terms of COD removal, which increases with increasing temperature. ,, Thus, the role of the temperature is vital for not only the energy generation performance of MFCs but also wastewater treatment.…”
Section: Resultsmentioning
confidence: 96%
“…Electrochemical examination showed that the MFC operated at 15 °C experienced lower anodic resistance than MFC at 25 °C, which can be related to the psychrophilic microscopic organisms Geobacter psychrophilus P35­(T) and Simplicispira psychrophila LMG 5408­(T) in anodic biofilms . A number of investigators have related power output enhancement with the increase in the temperature as a result of improvement in membrane permeability and microbial digestion and lowering of ohmic resistance because of the high conductivity of the liquid electrolyte. In addition, various research groups have tried to decrease the startup time using different approaches, such as changing the configurations and changing the working parameters. For example, a glass fiber separator was used to decrease the startup time from 10 to 8 days .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest COD removal efficiency of 84% was observed at an operating temperature of 40 °C. Tee et al ( 2018 ) studied the performance of MFC with an adsorption system (MFC-AHS) and palm oil mill effluent as a substrate under various operating temperatures. The optimum operating temperature for such a system was found at 35 °C.…”
Section: Performance Improvement For Biomass-fueled Mfcsmentioning
confidence: 99%
“…The optimum operating temperature for such a system was found at 35 °C. Also, results revealed that the maximum current density could increase linearly with the temperature at a rate of 0.1772 mA/m 2 /°C, whereas maximum PD was in a polynomial function (Tee et al 2018 ). Larrosa et al ( 2010 ) investigated single-chambered and dual-chambered MFC operation at different temperatures ranging from 4 to 35 °C.…”
Section: Performance Improvement For Biomass-fueled Mfcsmentioning
confidence: 99%